Double Centrifugation Versus Single Centrifugation of Bone Marrow Aspirate Concentrate in Sinus Floor Elevation: A Pilot Study - Oliveira, Thiago Altro de; Aloise, Antonio Carlos; Orosz, Jose Eduardo; Mello e Oliveira, Rafael de; Carvalho, Paulo de [UNESP]; Pelegrine, Andre Antonio (Quintessence Publishing Co Inc, 2016)
Purpose: To evaluate the regenerative results of the addition of bone marrow aspirate concentrate, using a single or double centrifugation protocol, to a xenogeneic bone graft in sinus floor elevation. Materials and Methods: Using a randomized, controlled pilot study design in 15 consecutive patients, sinus floor elevation procedures were performed with a xenogenous bone graft alone (control group, CG) or associated with bone marrow aspirate concentrate obtained by single centrifugation (single centrifugation group, SCG) or double centrifugation (double centrifugation group, DCG). In the patients in the single and double centrifugation groups, bone marrow was harvested from the iliac bone. Six months after the grafting procedures, bone biopsy specimens were obtained during implant placement and were analyzed by histomorphometry. Results: Histomorphometric analysis revealed a great amount of vital mineralized tissue in SCG followed by DCG when compared with the CG (38.44 +/- 12.34%, 34.63 +/- 9.84%, and 27.30 +/- 5.55%, respectively). SCG and DCG presented smaller amounts of nonvital mineralized tissue when compared with the CG (13.70 +/- 7.50%, 19.63 +/- 8.35%, and 22.79 +/- 9.60%, respectively), thus presenting higher levels of resorption. Although these differences were not statistically significant (P > .05), a tendency toward bone gain in the experimental groups (SCG and DCG) was found. All groups (SCG, DCG, and CG) showed similar levels of nonmineralized tissue (47.87 +/- 6.31%, 45.73 +/- 7.33%, and 49.90 +/- 7.64%, respectively). Conclusion: This pilot study indicates that the clinical use of bone marrow aspirate concentrate, obtained by either a single or double centrifugation process, combined with a xenograft for maxillary sinus elevation seems to result in more adequate bone repair. However, clinical trials with a larger number of patients are required. INT J ORAL MAXILLOFAC IMPLANTS 2016; 31: 216-222. doi: 10.11607/jomi.4170
Keywords: bone marrow; bone substitutes; clinical research; sinus floor augmentation